Simulações computacionais para estimativa da influência do crescimento urbano na formação de zonas inundáveis adjacentes ao Córrego do Monjolo, em Patos de Minas, MG - Caixeta, Ana Clara Mendes (2013)
Over the years, urban growth occurred in regions close to watersheds, making difficult the recharge areas of these basins and having consequences as urban flooding. Based on the study of urban watersheds, this work aims to estimate and delineate floatable areas around Monjolo Stream in Patos de Minas. Thus, from the application of hydrologic models (Method Santa Barbara) and hydraulic (kinematic wave) in computer flooding simulation, for different urbanization growth scenarios from remaining area of the basin, extreme floods situations were defined, which are the mimínas (approximately 2000 m² of envelopment and faster recovery time area) and maximum (return time of 100 years with the highest envelopment areas). Furthermore, this study verified the effects, on basin macro drainage, different rates of permeable areas in occupied allotments. In these simulations, we observed the appearance of adjacent flooding to the artificial watercourse, proving that for certain precipitation and basin urbanization scenarios, the overflow occurs at some points of its extension. With the base of inundograma significant widening, it was observed that there is an evident trend of longer lasting floods, with basin growing occupation. Analysing the simulation results, it was possible to establish a suggested maximum occupancy rate of 55% for the basin. This study also proposes the adoption of a minimum permeable area rate of at least 37% in future allotment, with 100% urbanization of the remaining area in order to prevent flooding on the Stream Monjolo Basin. This work analysis and observations, can be used by gestors to a more suitable urban planning, regards the basin occupation.